Recovery of Nd3+ and Dy3+ from E-Waste Using Adsorbents from Spent Tyre Rubbers: Batch and Column Dynamic Assays - Miguel Nogueira; Inês Matos; Maria Bernardo; Filomena Pinto; Isabel Fonseca; Nuno Lapa (Molecules)
This paper investigates the use of spent tyre rubber as a precursor for synthesising adsorbents to recover rare earth elements. Through pyrolysis and CO2 activation, tyre rubber is converted into porous carbonaceous materials with surface properties suited for rare earth element adsorption. The study also examines the efficiency of leaching rare earth elements from NdFeB magnets using optimised acid leaching methods, providing insights into recovery processes. The adsorption capacity of the materials was assessed through batch adsorption assays targeting neodymium (Nd3⁺) and dysprosium (Dy3⁺) ions. Results highlight the superior performance of activated carbon derived from tyre rubber following CO2 activation, with the best-performing adsorbent achieving maximum uptake capacities of 24.7 mg·g⁻1 for Nd3⁺ and 34.4 mg·g⁻1 for Dy3⁺. Column studies revealed efficient adsorption of Nd3⁺ and Dy3⁺ from synthetic and real magnet leachates with a maximum uptake capacity of 1.36 mg·g⁻1 for Nd3⁺ in real leachates and breakthrough times of 25 min. Bi-component assays showed no adverse effects when both ions were present, supporting their potential for simultaneous recovery. Furthermore, the adsorbents effectively recovered rare earth elements from e-waste magnet leachates, demonstrating practical applicability. This research underscores the potential of tyre rubber-derived adsorbents to enhance sustainability in critical raw material supply chains. By repurposing waste tyre rubber, these materials offer a sustainable solution for rare earth recovery, addressing resource scarcity while aligning with circular economy principles by diverting waste from landfills and creating value-added products.